(3MGTjI Ydi eNJUQ GdYVOjs - (3GdLQLGfj, GdTQja, Ydj Hf eMeO Hf Ydj, J (B816 (3g`s
(3ChdgG (B:s
... (3bhdg GdMeO ddg GdQDha , GdJSejI HGdJMejO aj eaJJM GdcdGe hGbJaGA deG hQO aj GdCNHGQ hGbJOGA HWQjbI GdCNHGQ hGOGA dHYV Mbhb eG GSJZQbJg ef VQhH GdEMSGf GdJj ef LedJgG GdJhajb HeKd gPG GdJUfja GdYXje (B...s
(3BNQgG (B:s
... (3bhdg hbjd (B.. (3Ydi GdGNJdGa aj GdCSHGH eY CfgG eJab YdjgG Pdc Ef JMbb Yf GdTQW GdTQYj HeG YO GdCSHGH hdG jdRe GYeGd MGdgG dCfgG bO YdeJ cdgG gGgfG aQY Yf cJGHJg dCLd faS GdYHO (B. (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ddRQcdj (B5/ 7s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdfMhs